Nursing undergraduates' perceptions of digital health (Research, Society and Development, 2025)
Objectives: To understand nursing undergraduates' perceptions of DS. Method: This was a cross-sectional, exploratory, and qualitative study conducted with eighth-semester nursing undergraduates at a university in São Paulo. Results: Regarding the perception of DS, 71.9% believe that nursing is related to digital issues, and 91.2% consider learning these technologies essential. Electronic medical records and artificial intelligence were highlighted as priorities, while topics such as remote monitoring and health education were less valued. Discussion: The data highlight a gap in academic training for DS, with little specific content in the curriculum. Although they recognize the relevance of technology, many students expressed uncertainty regarding the practical use of digital tools, reflecting insufficient training. Conclusion: The research demonstrated the urgent need to improve SD training for future nurses, preparing them for the technological challenges of clinical practice.